Optimizing E. coli as a formatotrophic platform for bioproduction via the reductive glycine pathway - Kim, Seohyoung; Giraldo, Néstor; Rainaldi, Vittorio; Machens, Fabian; Collas, Florent; Kubis, Armin; Kensy, Frank; Bar-Even, Arren; Lindner, Steffen N. (Frontiers in Bioengineering and Biotechnology, 2023)
Microbial C1 fixation has a vast potential to support a sustainable circular economy. Hence, several biotechnologically important microorganisms have been recently engineered for fixing C1 substrates. However, reports about C1-based bioproduction with these organisms are scarce. Here, we describe the optimization of a previously engineered formatotrophic Escherichia coli strain. Short-term adaptive laboratory evolution enhanced biomass yield and accelerated growth of formatotrophic E. coli to 3.3 g-CDW/mol-formate and 6 hours doubling time, respectively. Genome sequence analysis revealed that manipulation of acetate metabolism is the reason for better growth performance, verified by subsequent reverse engineering of the parental E. coli strain. Moreover, the improved strain is capable of growing to an OD600 of 22 in bioreactor fed-batch experiments, highlighting its potential use for industrial bioprocesses. Finally, demonstrating the strain’s potential to support a sustainable, formate-based bioeconomy, lactate production from formate and CO2 was engineered. The optimized strain generated 1.2 mM lactate—10 % of the theoretical maximum—providing the first proof-of-concept application of the reductive glycine pathway for bioproduction.